Mortality among individuals with substance use disorder—does violent criminal behavior have an impact? - Jakobsson, Joakim; Karlsson, Anna; Håkansson, Anders; Hofvander, Björn (Frontiers in Psychiatry, 2024)
IntroductionUnderstanding violent criminality and its impact on health and eventually the risk of premature mortality is important for efficient future interventions. This study aimed to explore the effect violent criminality had on premature mortality (i.e., death before the age of 65) among individuals with substance use disorders (SUDs).MethodsThe cohort was created by identifying all Swedish patients diagnosed with SUD between the first of January 2013 and 31st of December 2014. The individuals were split into three age categories.ResultsThere were significant differences in standard mortality rates (SMR) in the cohort compared to the general Swedish population across the three age categories. We found differences between the SMRs for individuals convicted of violent and nonviolent crimes in the two younger age categories [age 15–29: violent crime (42.4) vs. non-violent crime (36.6), age 30–44: violent crime (28.0) vs. non-violent crime (23.0)]. A Cox regression analysis showed that each conviction of a violent crime increased the hazard ratio (HR) of premature mortality significantly [age 15–29; HR = 1.10 (95% CI: 1.04–1.17), age 30–44; HR =1.06 (95% CI: 1.03–1.09)]. After correcting for non-violent crimes, the increased risk only remained for the youngest group [HR = 1.06 (95% CI: 1.00–1.13)].DiscussionThis study suggests that criminal behavior constitutes a proxy for the risk behaviors that increase the risk of premature mortality among young individuals with SUD even after controlling for confounders. Longitudinal studies, examining time-dependent risks and protective influences, are needed to explain the different pathways and processes leading to the amplified premature mortality in the groups.